A construção do ator "Dilma" em charges do jornal Folha de São Paulo - Melo, Priscila Florentino de (2012)
This work analyzes the construction of the actor Dilma Rousseff in carttons published by the Section Opinion of the Newspaper Folha de São Paulo, using the basis of the semiotic analysis. The analysis happens on the relation between elements of the plane of content and the plane of literal expression. We observe the construction of the actor “Dilma” in its relation however with the actor “Lula” however with the actor “party” that they composed its allied base of campaign. We describe the actantial, thematic and pathetic papers of the actors, the instauration of figures and subjects of the discursive level of the texts as well as the chromatic, eidetic and topological components which compose the plan of expression of the carttons. In this manner, when analyzing the correlation between the plans of expression and literal content, apprehends the semi-symbolic relation that, in the texts, is established. We still intend to establish a parallelism between carttons and its dialogue with opinion articles published in the Section Opinion of the Newspaper Folha de São Paulo.